The importance of Hungarian melon (Cucumis melo L.) landraces, local types and old varieties (Review) - Szamosi, Cs. (International Journal of Horticultural Science, 2005)
While supermarkets devote whole aisles to hybrids, traditional varieties are hard to find, and becoming scarcer day by day. Unfortunately, countless old melon varieties have already been lost. Luckily we succeded in collecting most of these varieties, and thus conserving them in Gene Banks. Landraces, local types, and old breed races show many characteristics that could be useful in organic farming. It is important to get acquainted with these varieties and cultivars, because they have greatly adapted to the climatic and pedological conditions of the Carpathian basin. Therefore their conservation is essential for the protection of Hungarian genetic variability. With the help of utilising our landraces in organic farming; careful selection; and the usage of marketing strategy in order to enhance quality features, such as unique flavour; we could reclaim the one-time excellent reputation of Hungarian melon.